2018
DOI: 10.1371/journal.pone.0202885
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 does not halt osteoporotic bone loss in ovariectomized rats

Abstract: Osteoporosis (OP) is a systemic skeletal disorder, manifesting with a reduction in bone mass and deterioration of the microarchitecture. Mesenchymal stem cells (MSCs) have an innate ability to differentiate into several cell types, including osteoblasts (OB). Ginsenoside Rb1 (GRb1) is an ethanol extract from ginseng and contains a highly concentrated form of ginsenoside. GRb1 shows extensive beneficial health effects such as anti-oxidative and anti-inflammatory functions, modulating the immune system and inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Moreover, ginsenoside Rg1 countervailed the decreased BMD in OVX rats [ 17 ], ginsenoside Rb2 revealed anti-osteoporosis effect by reducing oxidative damage and bone resorbing cytokines in osteoblast cells [ 19 ]. In contrary, ginsenoside Rb1 increased osteogenic differentiation and osteogenic proteins, however, did not halt osteoporotic bone loss in OVX rats [ 20 ]. However, despite accumulating data on the effect of P. notoginseng on OP in rats, the effect of P. ginseng on postmenopausal OP is not clearly defined; thus, we investigated the effect of P. ginseng on this disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ginsenoside Rg1 countervailed the decreased BMD in OVX rats [ 17 ], ginsenoside Rb2 revealed anti-osteoporosis effect by reducing oxidative damage and bone resorbing cytokines in osteoblast cells [ 19 ]. In contrary, ginsenoside Rb1 increased osteogenic differentiation and osteogenic proteins, however, did not halt osteoporotic bone loss in OVX rats [ 20 ]. However, despite accumulating data on the effect of P. notoginseng on OP in rats, the effect of P. ginseng on postmenopausal OP is not clearly defined; thus, we investigated the effect of P. ginseng on this disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that ginsenosides inhibit osteoclastogenesis and reduce bone resorption [ 15 18 ], although this is not uniformly the case [ 36 , 37 ]. The histomorphometric data in the present study showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenosides also have osteoprotective properties. Several studies have demonstrated that Rb1, Rh1, Rg3, and Rg5 stimulated osteoblast differentiation in vitro [ 255 , 256 , 257 , 258 ]. Furthermore, Rb1 and Rg3 inhibited osteoclastogenesis by suppressing RANKL-induced activation via modulating MAPKs and NF-κB pathways in vitro, but only Rg3 was able to alleviate bone mineral density loss in vivo [ 259 , 260 ].…”
Section: Natural-compound-based Treatments For Oa Therapymentioning
confidence: 99%